A Novel Dual Bruton's Tyrosine Kinase/Janus Kinase 3 Inhibitor Wj1113 and its Therapeutic Effects on Rheumatoid Arthritis - Chunyu Zhang; Fangfang Lai; Hang Gong; Shuying Li; Nan Xiang; Liuyi Que; Nina Xue; Mengyao Hao; Enjia Zhou; Xiaojian Wang; Taigang Liang; Jing Jin (MedComm)
ABSTRACT Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by joint inflammation and tissue damage, driven by dysregulated cytokine signaling and immune cell hyperactivation. Bruton's tyrosine kinase (BTK) mediates pathogenic B‐cell activation and autoantibody production, while Janus kinase 3 (JAK3) orchestrates cytokine‐driven inflammation through signal transducer and activator of transcription 5 (STAT5) phosphorylation, exacerbating macrophage and monocyte activation. Here, we report Wj1113, a novel dual inhibitor that potently blocks BTK (IC50 = 0.7 nM) and JAK3 (IC50 = 26.2 nM). Wj1113 inhibits B‐cell activation via BTK blockade and suppresses JAK3‐dependent STAT5 phosphorylation, reducing proinflammatory cytokine secretion and monocyte chemotaxis. In vitro, it suppresses macrophage activation and modulates inflammatory mediator expression. In the collagen‐induced arthritis mouse model, Wj1113 treatment dose‐dependently reduces joint inflammation, macrophage infiltration, and levels of TNF‐α (tumor necrosis factor‐α), IL(interleukin)‐6, anti‐cyclic citrullinated peptide antibody (ACPA) and rheumatoid factor (RF), while elevating anti‐inflammatory IL‐10. Histopathological and micro‐CT analyses confirm attenuation of cartilage/bone erosion and synovial hyperplasia. Mechanistically, Wj1113 inhibits BTK/JAK3 signaling in vivo and alleviates arthritis in joints. Collectively, these findings establish Wj1113 as a promising dual‐target therapeutic candidate for RA, addressing both B‐cell and cytokine‐driven pathogenic pathways.